Emerging Perspectives of RNA N6-methyladenosine (m6A) Modification on Immunity and Autoimmune Diseases - Tang, Lipeng; Wei, Xingyan; Li, Tong; Chen, Yi; Dai, Zhenhua; Lu, Chuanjian; Zheng, Guangjuan (Frontiers in Immunology, 2021)
N6-methyladenosine (m6A) modification, the addition of a methylation decoration at the position of N6 of adenosine, is one of the most prevalent modifications among the over 100 known chemical modifications of RNA. Numerous studies have recently characterized that RNA m6A modification functions as a critical post-transcriptional regulator of gene expression through modulating various aspects of RNA metabolism. In this review, we will illustrate the current perspectives on the biological process of m6A methylation. Then we will further summarize the vital modulatory effects of m6A modification on immunity, viral infection and autoinflammatory disorders. Recent studies suggest that m6A decoration plays an important role in immunity, viral infection and autoimmune diseases, thereby providing promising biomarkers and therapeutic targets for viral infection and autoimmune disorders.